Sorptive properties of hydrogel dressings and their antimicrobial action after saturation with tetracyclines - Vlizlo, V.; Ostapiv, D.; Kuzmina, N.; Mysak, A.; Nosova, N.; Varvarenko, S.; Samaryk, V.; Stybel, V.; Ostapiv, R. (Regulatory Mechanisms in Biosystems, 2025)
Due to the war in Ukraine and a high number of wounds among combatants, civilians, and also working and domestic animals, the need for high-quality and effective dressing material is extremely relevant. Therefore, the objective of our study was to in vitro examine the sorptive properties of hydrogel dressings that we made and their antimicrobial action after saturation with tetracycline antibiotics. The sorptivity was determined by submerging the hydrogel samples for 1 h in water, wound exudate model, blood, 5% solution of oxytetracycline hydrochloride, and chlortetracycline. The presence of tetracyclines in the samples of hydrogel dressings was studied using high-performance fluid chromatography; the uniformity of their antibiotic saturation was examined under a light microscope; and the antimicrobial properties were studied by incubation with Staphylococcus aureus , Escherichia coli , and Pseudomonas аeruginosa . The conducted studies revealed that the hydrogel dressings had good sorptivity. During one hour of contact of hydrogel with water, and also blood exudate model, and blood, which are the main components of wounds, the examined samples were actively saturating. After sorption of the dressings with 5% solutions of tetracyclines, we determined a 1.34 – 1.90 time increase in their mass. Moreover, the content of oxytetracycline hydrochloride and chlortetracycline in the structure of hydrogel was chromatographically confirmed, and histological analysis even revealed that the samples were uniformly filled with antibiotics. The hydrogel dressings loaded with oxytetracycline hydrochloride containing 98.6% and 94.5% active agent and chlortetracycline hydrochloride with an active agent content of 99.9% exerted notable antimicrobial action toward the microorganisms S. аureus , E. coli , and P. аeruginosa . Thus, the hydrogel sheets had good sorptivity and their saturation with tetracyclines led to effective elimination of the microorganisms. Hydrogel dressings with antibacterial drugs can be used to treat wound infections, because they enable a quick application of a necessary therapeutic concentration of med i cal compounds to the wound surface. Further studies will focus on the efficacy of hydrogel dressings applied directly to animal wounds.